Communicaton Audits: Adding Value and Social Impact to Agricultural Communications - Joy N. Goodwin; Andrea Davis; Ricky W. Telg (Journal of Applied Communications, 2014)
Communication audits can enhance the communication efforts of agricultural organizations. Communication audits identify what is being done well, what is not being done well, and how communication efforts can be improved. In addition to communication audits, usability testing adds value to understanding the use of communication materials by a target audience. Taking steps to improve communications, based on the findings of communication audits and usability testing, can help organizations improve their brand consistency, social impact, and overall communication. This paper provides a rationale for communication audits and provides procedures, tips, and experiences for the communication practitioner.
Keywords: communication audit; usability testing; branding; identity guide